2009
DOI: 10.1002/ptr.2798
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of locally applied carvacrol gel on ligature‐induced periodontitis in rats: a tapping mode AFM study

Abstract: The aims of this study were to test a locally applied carvacrol gel and determine its efficacy preventing alveolar bone loss in experimental periodontitis in rats by regular methodology to validate applicability the atomic force microscopy (AFM) as a novel morphology method on this model. Wistar rats were subjected to ligature around second, upper-left molars. Animals were treated carvacrol gel topically (CAG), immediately after Experimental Periodontitis Disease induction for 1' three-times/day for 11 days. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 19 publications
5
48
0
Order By: Relevance
“…The chemical compositions of essential oils in the present study, was consistent with other reports (Packer & Luz, 2007;Costa et al, 2008;Botelho et al, 2009b). In fact, essential oils contents and compositions could differ greatly even in the same genus, as well as in different ripening stage and different organs (Tirado et al,1995;Stashenko et al, 1996).…”
Section: Phythochemical Screening and Antimicrobial Activity Of Essensupporting
confidence: 92%
“…The chemical compositions of essential oils in the present study, was consistent with other reports (Packer & Luz, 2007;Costa et al, 2008;Botelho et al, 2009b). In fact, essential oils contents and compositions could differ greatly even in the same genus, as well as in different ripening stage and different organs (Tirado et al,1995;Stashenko et al, 1996).…”
Section: Phythochemical Screening and Antimicrobial Activity Of Essensupporting
confidence: 92%
“…19) However, the effects of carvacrol on osteoclastogenesis, and underlying molecular mechanisms have not been explored yet. This study analyzes the effects of carvacrol on osteoclast formation induced by RANKL and LPS, as well as its effects on RANKL signaling involved in osteoclastogenesis.…”
Section: )mentioning
confidence: 99%
“…Although very few studies have examined the role of natural products in controlling periodontitis, Botelho et al 8 recently tested a locally-applied carvacrol gel (Lippia sidoides derivatives) and determined its efficacy in controlling bone loss in experimental periodontitis in rats. The authors showed evidence that this natural chemical agent preserved alveolar bone resorption and showed anti-inflammatory and antibacterial activities in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Natural products represent a significant source of substances for use in the control of oral diseases, especially in managing plaque-related diseases such as gingivitis. [4][5][6][7][8] Brazil is said to be the richest country in the world in terms of its biodiversity, and few data are available about the pharmacological and chemical potential of its flora as a source of new medicines. In previous investigations developed by our research group, Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%